The Pseudo-Culture: Financial Management Risk In Village Government - Noorlailie Soewarno, Lina Nasihatun Nafidah, Bambang Tjahjadi, (Opción, 1970)
Indonesia’s mutual cooperation culture through active community participation in village development. However, the role of these positive values in society is fading and giving rise to pseudo-culture. The culture of mutual cooperation in the life of social communities in rural areas has experienced a decline values in the cultural caused by the existence of a dominant political attitude by the leadership of power in the countryside resulting in a decrease in community trust in the management of rural development. Political risks in the management of village finance is a threat in the cultural values of the community cooperation become pseudo